Sesquiterpene Lactones Advances in their Chemistry and Biological Aspects - Sülsen, Valeria Patricia; Martino, Virginia Susana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book addresses chemical and biological aspects related to sesquiterpene lactones (STLs). Experts in different fields have been invited to contribute on this class of compound's chemistry, isolation and identification, biological activities (antibacterial, antifungal, antiviral, antitrypanosomal, antileishmanial,antiplasmodial, antiproliferative and antiinflammatory), synthesis, biosynthesis, derivatization and QSAR analysis. Taxonomic and chemotaxonomic aspects related to the Asteraceae family are also contributed. The book begins by describing the chemical characteristics of STLs, their classification in different skeleton types, synthesis, distribution in nature and their most important biological properties. An overview of the group's main representatives, based on their importance for human health, as well as an update of the most recently isolated STLs, follow. The authors also provide an overview of the most common methods described in the literature for the extraction, purification, identification and structure elucidation of STLs, while also highlighting more recently developed methods. Furthermore, experts in the field provide an in-depth discussion of the most commonly employed in vitro and in vivo antiprotozoal assays against the different stages of parasites, as well as STLs' properties as anticancer agents in numerous cancer cell lines and animal models. Lastly, the book presents examples of the in vitro and in vivo activity of STLs and their mechanism of antiprotozoal action, together with an analysis of ultrastructural alterations, observed using TEM techniques. The book is aimed at scientists working on natural products: both those investigating this particular group of compounds and those who wish to further explore its potential as new drugs for medical conditions such as protozoal diseases and cancer.
Part1. Chemical and biochemical aspects of sesquiterpene lactones -- Chapter1. Overview -- Chapter2. Ancient and modern concepts about the asteraceae taxonomy -- Chapter3. Chemotaxonomic study of sesquiterpene lactones of asteraceae: classical and modern methods -- Chapter4. Biosynthesis of sesquiterpene lactones in plants and metabolic engineering for their biotechnological production -- Chapter5. Chemistry of sesquiterpene lactones -- Chapter6. Analytical procedures -- Chapter7. Spectroscopic methods for the identification of sesquiterpene lactones -- Part2. Biological activities of sesquiterpene lactones -- Chapter8. Antitrypanosomal and antileishmanial activities -- Chapter9. Antiplasmodial activity -- Chapter10. Mode of action on trypanosoma and leishmania spp -- Chapter11. Contribution of microscopy for understanding the mechanism of action against trypanosomatids -- Chapter12. Effects on other microorganisms -- Chapter13. Antiproliferative and cytotoxic activities -- Chapter14. Anti-inflammatory activity -- Part3. Sesquiterpene lactones: medicinal chemistry approach -- Chapter15. Structure-activity and activity-activity relationships of sesquiterpene lactones.
Keywords: Medicinal chemistry; Pharmacology; Chemistry, Organic; Biochemistry; Medicinal Chemistry; Pharmacology; Organic Chemistry; Biochemistry